Antibacterial activity of Chrysophyllum albidium seed oil extract on pathogenic Staphylococcus aureus - Martin C. Onuigbo; Chimere Y. Ukegbu; Kelechukwu C. Uzoigwe (Narra X, 2023)
Antimicrobial resistance in Staphylococcus aureus has continued to rise and has become a general medical problem. Thus, the objective of this study was to use the Chrysophyllum albidum seed extract as an antibiotic against pathogenic Staphylococcus aureus. The antimicrobial impact of Chrysophyllum albidum seed oil on pathogenic Staphylococcus aureus from various sources were explored utilizing agar well dissemination strategy. The oil was separated utilizing the Soxhlet extraction strategy with n-hexane as the solvent. The oil extract was then prepared in various concentrations (62.5–500 mg/mL) and tested against three different pathogenic isolates of Staphylococcus aureus. At the highest concentration (500 mg/mL), the oil extract yielded 22–24.6 mm inhibition zones. Meanwhile, at the lowest concentration (62.5 mg/mL), the inhibition zones achieved were 14.6–16 mm. The minimum inhibitory concentration was 125 mg/mL, while the mean minimum bactericidal concentration was 250 mg/mL. In conclusion, our data suggested that the oil from seeds of Chrysophyllum albidum has antibacterial activities against Staphylococcus aureus and this needs to be further studied.